Belajar Membaca Bagi Anak Usia Dini: Stimulasi Menumbuhkan Minat Baca Anak (THUFULA, 2014)
Teaching reading in early childhood is not something that is bannedaltogether. Not teaching reading in early childhood recommended mostlyeducational experts or psychologists should be understood thoroughly if inearly childhood assistance is conditioned by compulsion that would burden thechildren feel under pressure to do reading. While they are still in childhoodthat still need games and fun atmosphere. Teaching reading in early childhoodmay be provided with a pleasant conditioning and aims to foster children’sinterest in reading. So, through conditioning without the word “must be readat the time”, a companion will lead and stimulate children’s interest in readingactivities. Thus, by itself the child will be encouraged curiosity to learn to read.